Internal communication changes in the Croatian police in the decade of intensive democratization: a comparison between 2010 and 2020 = Spremembe internega komuniciranja hrvaške policije v desetletju intenzivne demokratizacije : primerjava med letoma 2010 in 2020 - Dunaj, Ana Marija (Revija za kriminalistiko in kriminologijo, 2023)
This paper aims to determine changes to the internal communication in the police organization in Croatia over a ten-year period. The research is based on a survey conducted on a convenient sample of respondents – 2010 (n = 1,250) and 2020 (n = 1,296). The respondents, i.e. police officers, filled in a questionnaire that measures eight dimensions of satisfaction with internal communication. The results of discriminant analysis reveal that there is a difference in satisfaction with internal communication in the two waves of research. Statistically significant are the differences between respondents in 2010 and 2020 for all dimensions. The contribution of the paper is its monitoring of changes in the satisfaction of police officers in Croatia with internal communication. The investigation of changes in communication is extremely important because police organizations, especially in transition countries, have changed frequently.